Understanding finance : (Harvard Business School Pub., 2007)
The Pocket Mentor" series offers immediate solutions to common challenges managers face on the job every day. Each book in the series is packed with handy tools, self-tests, and real-life examples to help you identify your strengths and weaknesses and hone critical skills. Whether you're at your desk, in a meeting, or on the road, these portable guides enable you to tackle the daily demands of your work with greater speed, savvy, and effectiveness.